Digital Leadership in SMEs: A Bibliometric Review of Research Trends, Thematic Evolution, and Emerging Strategic Perspectives - Darwish Tahiry (International Journal of Educational Administration, Management, and Leadership, 2026)
Digital leadership has become increasingly important in Small and Medium-sized Enterprises (SMEs) as firms face growing pressure to adapt to digital transformation, innovation demands, and changing competitive conditions. However, the literature on digital leadership in SMEs remains fragmented across related themes such as technology adoption, innovation capability, and business performance. This study aims to map the development of research on digital leadership in SMEs through a bibliometric analysis of Scopus-indexed journal articles published between 2021 and 2026. The dataset consisted of 453 English-language journal articles within the Business, Management and Accounting subject area. Descriptive analysis was conducted using Scopus Analyze Search Results, while thematic mapping was performed using VOSviewer through keyword co-occurrence analysis. The findings show that research on digital leadership in SMEs has grown rapidly, particularly after 2023, and has developed as an interdisciplinary and internationally distributed field. The thematic structure remains strongly anchored in digital transformation and digital technologies, while digital leadership appears as an emerging but increasingly strategic theme linked to innovation capability, competitive advantage, and organizational performance. The study suggests that the field is shifting from a focus on operational digital adoption toward a stronger concern with leadership capability and long-term competitiveness. These findings contribute to a clearer understanding of the intellectual structure of the field and provide directions for future research and practice.